Explaining local brand skincare purchase intention in Indonesia - Fitriana, Ana; Afifah, Nur; Mustaruddin, Mustaruddin (Institute of Computer Science (IOCS), 2024)
This study investigates how perceived brand globalness and localness influence consumer-brand identification and purchase intention for local skincare brands in Indonesia. A quantitative approach was employed, collecting data from 218 Indonesian respondents through an online survey. Structural equation modeling was used to analyze the conceptual model and test hypotheses by using AMOS 22 software. The results reveal that perceived brand localness positively affects consumer brand identification and purchase intention for local skincare brands, while perceived brand globalness has no significant impact. Furthermore, consumer brand identification mediates the influence of perceived brand localness on purchase intention. These findings suggest Indonesian consumers value the localness of skincare products more than their global presence, possibly due to the personal nature of skincare and desire for locally-tailored offerings. As the Indonesian skincare market continues growing, leveraging perceived brand localness emerges as a key strategy for local brands to foster consumer identification and drive purchase intent